Media battles in the cybersphere: analyzing news and social media agendas during the 2015 Greek bailout referendum - Sergidou, Nelly-Maria; Triga, Vasiliki; Tsapatsoulis, Nicolas (Frontiers in Political Science, 2025)
On June 27, 2015, the Greek coalition government, led by the left-wing SYRIZA party, announced the July 5th referendum, asking citizens to decide on the adoption of the EU-proposed economic plan. Referendums in Greece are infrequent, and this decision sparked various interpretations of the motives behind it. In events like the 2016 US presidential elections and the Brexit referendum of the same year, public opinion, especially as expressed on platforms like Twitter, often diverged from the narrative set by the news media agenda. The outcome of the Greek referendum reflected Twitter users’ preferences more closely, surprising many and challenging the traditional role of news media in shaping public opinion. This paper revisits the 2015 Greek referendum, comparing topics discussed in news media with those on Twitter to understand whether the disparity between the two platforms resulted from the dominance of news media agenda-setting or other factors, such as Twitter’s inclination toward alternative voices. The study employs content analysis and topic modeling on a dataset comprising news articles and tweets. Results indicate that the news media agenda predominantly influenced topics discussed by “YES” supporters on Twitter, while it played a less significant role in shaping the topics discussed by “NO” supporters during the 2015 Greek referendum.